2013
DOI: 10.1093/ejcts/ezt230
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet therapy at the time of coronary artery bypass grafting: a multicentre cohort study

Abstract: Preoperative APT is associated with increased bleeding and greater transfusion requirements after CABG. Clopidogrel exposure is associated with greater reoperation rates and is an independent risk factor for severe postoperative bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 23 publications
1
20
1
Order By: Relevance
“…3,4 This effect has been attributed in part to the increased bleeding risk and perioperative stent thrombosis that results from an imperfect balance of perioperative anticoagulation. 5 Improved understanding of perioperative anticoagulation and optimal timing of surgery after PCI-S may decrease the rate of perioperative complications, with some reports suggesting no early adverse effects. 6,7 …”
mentioning
confidence: 99%
“…3,4 This effect has been attributed in part to the increased bleeding risk and perioperative stent thrombosis that results from an imperfect balance of perioperative anticoagulation. 5 Improved understanding of perioperative anticoagulation and optimal timing of surgery after PCI-S may decrease the rate of perioperative complications, with some reports suggesting no early adverse effects. 6,7 …”
mentioning
confidence: 99%
“…In a multi centre cohort study Kremke et al concluded that preoperative anti platelet is associated with increased bleeding and greater transfusion requirements after CABG. Clopidogrel was found to be an independent risk factor for severe post operative bleeding 10. Similarly Goldman et al in a multi centred randomised trial showed that preoperative aspirin is associated with more bleeding, transfusion requirements.…”
Section: Discussionmentioning
confidence: 84%
“…Given the association between P2Y 12 inhibitor use and surgical bleeding, the American College of Cardiology Foundation and American Heart Association advise discontinuation of clopidogrel for ≥5 days prior to elective CABG (class I recommendation, level of evidence [LOE] B). These guidelines reflect data from studies that associate perioperative clopidogrel exposure with increased bleeding, blood‐product transfusion, reoperation, and longer hospitalization, particularly if administered within 5 days prior to CABG …”
Section: Introductionmentioning
confidence: 93%